REALISTIC ANIMALS IN COLORED PENCIL - SNOWDON, BONNY (WALTER FOSTER PUB, 2021)
Learn to draw incredibly photorealistic pets, exotic animals, horses, and more with Realistic Animals in Colored Pencil in this follow-up to Realistic Portraits in Colored Pencil and Realistic Still Life in Colored Pencil.